A Method for the Determination of Weak Acid Concentration Based on Electrochemical Reduction of Benzoquinone. Issue 5 (1st January 2016) - Liu, Na; Wang, Yaotian; Xu, Xiaokun; Zhu, Zhihui; Han, Yinghui; Wang, Jianguo
Abstract : With the addition of a weak acid, a new prepeak occurs at a positive potential when quinone is reduced in an unbuffered solution. This prepeak was initially attributed to the protonation of a quinone anion radical. However, two prepeaks of the reduced quinone are detected in a solution containing dilute acetic acid and sodium dihydrogen phosphate. Evidently, the two prepeaks could not be assigned to the protonation of the quinone anion radical. In the unbuffered solution, the pH near the electrode surface increases drastically during the electrochemical reduction of p -benzoquinone (BQ). Our previous work revealed that a steep change in pH near the electrode surface produces a new voltammetric wave in a dilute buffer solution. We suggest that the new prepeaks are generated by a drastic change in pH near the electrode surface. Weak acids can release protons and suppress the increase in pH on the electrode surface. Therefore, the height of the prepeak is proportional to the concentration of the weak acid but is independent of BQ. We then establish a differential pulse voltammetric method to measure the weak acid and acetic acid contents of two kinds of vinegars. Our results agree well with those measured through potentiometric titration.